At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
first deal with -3(m-2) and distribute the -3 to get -3m+6
then combine it with the first term which was 10
10-3m+6
add up the like terms
16-3m
now solve
16-3m=8
subtract 16 from both sides
16-16-3m=8-16
-3m=-8
divide by -3
m=8/3
then combine it with the first term which was 10
10-3m+6
add up the like terms
16-3m
now solve
16-3m=8
subtract 16 from both sides
16-16-3m=8-16
-3m=-8
divide by -3
m=8/3
Hey there!
10 - 3(m - 2) = 8
10 - 3(m) - 3(-2) = 8
10 - 3m + 6 = 8
16 - 3m = 8
-3m + 16 = 8
SUBTRACT 16 to BOTH SIDES
-3m + 16 - 16 = 8 + 16
SIMPLIFY IT!
-3m = -8
DIVIDE -3 to BOTH SIDES
-3m/-3 = -8/-3
SIMPLIFY IT!
m = 8/3
m = 2 2/3
Therefore, your answer is:
• m = 8/3
OR
• m = 2 2/3
Good luck on your assignment & enjoy your day!
~Amphitrite1040:)
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.